Community action for rural youth in Tanzania - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
This report comes from Arusha in northern Tanzania, where CADECT, a non-government organisation, is assisting young people and women through grassroots training, and group development. The report also includes comments from the Arusha district extension officer, who advocates the need for modern agricultural techniques to change the perception that farming is old-fashioned.